(untitled) (Balthazar, 2025)
This creative critical essay initiates from the writer’s existential question about the use of pronouns as expression of one’s own identity. Susan Sontag’s Under the Sign of Saturn and Primarily Women (original Dutch title: Voornamelijk Vrouwen) by the renowned Dutch novelist and philosopher Connie Palmen, are the essay books that guide her through the quest for one’s own voice. As Sontag’s writings on theory are brought into dialogue with Palmen’s autotheoretical personal essays to gain new insights into the styles of both, the question of pronouns and identity is explored through the contribution to knowledge and self-knowledge from these two major sorts of essay writing.